SEA WATER QUALITY OBSERVED FROM NUTRIENT ASPECT, DISSOLVED OXYGEN AND PH IN THE BANGGAI WATERS, CENTRAL SULAWESI - Marojahan Simanjuntak (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2012)
Banggai Waters, Central Sulawesi is very important because the waters is very rich in marine resources and its oceanographic conditions are affected by land and Banda Sea. This research was conducted in June-July 2011 using a research vessel Baruna Jaya VIII. The research objective was to determine water quality based on as an indicator of fertility waters and factors influencing the water quality. The parameters studied were phosphate, nitrate, silicate, dissolved oxygen, and acidity (pH). Water samples were collected using Niskin Bottle attached with CTD form three different depths i.e., surface (0-1 m), middle (20-100 m), and near bottom layer (100-200 m) at 14 stations. Concentrations of phosphate, nitrate, and silicate were analyzed according to the method of Strickland and Parsons. Dissolved oxygen concentrations were measured by Winkler method. The degree of acidity (pH) was measured with pH meter Cyber ​​Scan 300. The results indicated that nutrient concentrations were generally higher in eastern and southern waters. Phosphate concentrations ranged from 0,04–1.70 µg A/l; nitrate 0.28–27.23 µg A/l, and silicate 1.96–46.56 µg A/l. Dissolved oxygen concentrations ranged from 2.14–4.15 ml/l, and pH values ​​from 7.95–8.26. In reference to the quality standards set by the Ministry of Environment (KMNLH), the Banggai Waters, Central Sulawesi is still in good conditions for the life of various biota.. Keywords: water quality, fertility waters, nutrients, Banggai Waters